Personal Learning Letter Writing Model Using Exercise Technique Based on Curriculum 2006 KTSP - Nurwilah, Lilis Dewi; Sobari, Teti (IKIP Siliwangi, 2018)
The development of an educational curriculum is one part of educational reform. One of them is the competency-based curriculum. This curriculum emerges as an effort to perfect the learning strategy. This study refers to the Education Unit Level Curriculum. Therefore, the problem of this research is related to the learning system based on KTSP 2006. The research problem is limited to 3 aspects, namely (1) the preparation model of learning to write a personal letter; (2) the implementation of personal letter writing lessons with exercise techniques; (3) the result of a personal letter writing process. Furthermore, the authors also establish a hypothesis which reads: if the personalized vocabulary is taught by training techniques and in accordance with the syllabus and prepared learning plan, then the results will be satisfactory.